Nursing Students’ Satisfaction with Online Learning Experiences During Covid-19 Pandemic at Albaha University, Saudi Arabia - A. M. Ahmed, Waled (Sudan Journal of Medical Sciences, 2022)
Background: The teaching process in universities had faced several challenges during the COVID-19 pandemic. As most universities have shifted to online learning, this study aimed to assess nursing students’ satisfaction with online learning during the pandemic. Methods: This is a descriptive cross-sectional study; it was conducted among nursing students during the COVID-19 pandemic. The authors used an adopted online questionnaire to assess students’ satisfaction. The data were analyzed by SPSS software. Results: The study found that nursing students age was mainly between 22-24 years (78.9%), both male (46.1%) and female (53.9%) students. The nursing students’ satisfaction with online learning during COVID-19 was moderate (23.68%) to high (64.47%). A significant relationship was observed between students age and sex with satisfaction levels in online learning with a p-value less than 0.05. Conclusions: The study showed that the nursing students were satisfied with an online learning experience. Female students and those who are between 22-24 years have significantly higher levels of satisfaction.